(untitled) - Wilson, Earl R. (Boston, 2007)
Chapter 1 through 9 of this text focus on accounting and financial reporting issues of governmental entities at the state and local levels that follow the reporting model pre-scribed by GASB. Chapters 10 and 11 are similar in that they describe how decision makers can use audited annual financial statements,...
Keywords: Finance, Public,Nonprofit organizations,Nonprofit organizations; Accounting,Accounting.,Accounting; United States